Resiliensi Masyarakat Penyintas Bencana Alam pada Masa Pandemi Covid-19 di Kota Palu Sulawesi Tengah - Muhammad Fakhrur Razy; Yogi Suprayogi Sugandi; Muhammad Fedriansyah (Jurnal Sosiologi Andalas, 2022)
This study discussed the social resilience of natural disaster survivors during the Covid-19 pandemic. So it would discuss more about the live of natural disaster survivors in this era, as it was known that facing a pandemic they were faced with natural disasters that had a major impact on their lives. This study aimed to discuss how the social life of natural disaster survivors was and what factors affected the social resilience of disaster survivors during the pandemic. In this study, the author used a qualitative method with household groups of natural disaster survivors as informants, which had the categories of groups of households that had lost their homes, groups of households that have lost their homes and jobs, groups of households that had lost their homes and families and the last group of homes. households who have lost their homes, jobs and family members. The Findings were survivors of natural disasters during this pandemic having a good level of resilience with the support of several factors, namely Individual Factors, Social Support and spiritual.